Pembelajaran Jarak Jauh Berbasis Teknologi Informasi Dan Komunikasi - Miftahuljannah, Viona; Nasution, Muhammad Irwan Padli; Nasution, Wahyuddin Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of information and communication technology (ICT) has brought significant changes to the world of education, especially in the implementation of distance learning (PJJ). ICT-based PJJ allows the teaching and learning series to take place without space and time limitations, and provides easy access to digital learning resources. This article discusses the concepts, benefits, challenges, and strategies for implementing ICT-based PJJ, as well as the importance of infrastructure readiness, digital competence of educators and students, and adequate policy support. With the right approach, ICT-based PJJ can be an effective solution for equitable access to education and improving the quality of learning in the digital era.